2021
DOI: 10.1007/s10648-020-09585-3
|View full text |Cite
|
Sign up to set email alerts
|

Activity Achievement Emotions and Academic Performance: A Meta-analysis

Abstract: Achievement emotions are emotions linked to achievement academic, work, or sports activities (activity emotions) and their success and failure outcomes (outcome emotions). Recent evidence suggests that achievement emotions are linked to motivational, self-regulatory, and cognitive processes that are crucial for academic success. Despite the importance of these emotions, syntheses of empirical findings investigating their relationship with student achievement are scarce. We broadly review the literature on achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(168 citation statements)
references
References 140 publications
6
124
2
1
Order By: Relevance
“…Some philosophical notions of boredom emphasized its benefits [ 6 , 7 ] and also in the psychological literature, it has been argued that boredom can be considered functional, for example, in the context of willpower [ 8 ]. However, academic boredom in particular, has been shown to be a largely adverse emotional experience [ 6 ] and there is consistent empirical evidence that academic boredom is linked with a multitude of problematic academic outcomes, including higher levels of achievement-related anger, anxiety, and shame [ 9 , 10 ], reduced motivation and effort [ 11 , 12 , 13 ], lower academic achievement [ 10 , 14 , 15 , 16 , 17 ], and dropping out of school [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some philosophical notions of boredom emphasized its benefits [ 6 , 7 ] and also in the psychological literature, it has been argued that boredom can be considered functional, for example, in the context of willpower [ 8 ]. However, academic boredom in particular, has been shown to be a largely adverse emotional experience [ 6 ] and there is consistent empirical evidence that academic boredom is linked with a multitude of problematic academic outcomes, including higher levels of achievement-related anger, anxiety, and shame [ 9 , 10 ], reduced motivation and effort [ 11 , 12 , 13 ], lower academic achievement [ 10 , 14 , 15 , 16 , 17 ], and dropping out of school [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…When a student's personal goals and learning task are in congruence, then they experience the academic emotion of enjoyment (Linnenbrink, 2007). Moreover, during enjoyment student considers the learning situation as positively valued and controllable (Camacho-Morles et al, 2021). The academic emotion of enjoyment has been found to positively predict students' academic performance (Daniels et al, 2009).…”
Section: Academic Emotionsmentioning
confidence: 99%
“…mentalization and epistemic trust) should be taken into consideration in future research associated with learning environment. From the study perspective, it is important to raise the role of such personality traits in order to shed light on targeted interventions that may promote students' well being along with adaptive learning strategies (Ng & Vella-Brodrick, 2019;Camacho-Morles et al, 2021).…”
Section: Limitations and Future Implicationsmentioning
confidence: 99%
“…Regulating negative emotions (e.g., boredom) and supporting positive emotions (e.g., enjoyment) should thus facilitate successful SRL and support long-term engagement in SRL (Pekrun et al, 2002;Ben-Eliyahu and Linnenbrink-Garcia, 2015). Empirical research also indicates that emotions are a significant aspect of successful learning processes that lead to higher academic achievement (Camacho-Morles et al, 2021). For example, Perry et al (2001) showed in their longitudinal study that students with higher academic control reported less course boredom, were more motivated, used more strategies, and obtained higher course grades.…”
Section: Mindsets Self-concepts Emotions and Their Relationship To Strategy Knowledgementioning
confidence: 99%
“…So far, little is known about self-theories about SRL and their possible relationship to enjoyment or boredom in learning. This study focuses on boredom and enjoyment, as researchers showed that these emotions are of particular relevance for students' learning and academic achievement (Camacho-Morles et al, 2021). Hence, this paper aims to examine the role of students' mindsets and selfconcepts about SRL concerning their enjoyment and boredom about learning, strategy knowledge, and academic achievement.…”
Section: Introductionmentioning
confidence: 99%